2003
DOI: 10.1103/physrevlett.91.196102
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Resolution Imaging of the (001) Surface of UHV Cleaved MgO by Dynamic Scanning Force Microscopy

Abstract: The (001) surface of UHV cleaved single MgO crystals was imaged with dynamic mode scanning force microscopy. Large-scale images show various defects, like steps of mostly one atomic height, rectangular holes of nanometer size, and some complex adstructures. First time images with atomic resolution show one square ionic sublattice in its bulklike dimension with a corrugation of up to 40 pm along the <001> direction. Most images exhibit atomic point defects which appear as depressions including a few ionic latti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
127
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(138 citation statements)
references
References 28 publications
11
127
0
Order By: Relevance
“…For example, AFM images shown in fig. 1 in Barth & Henry (2003) demonstrate that irregular adstructures, reminiscent of debris on the rough surface shown in figure 6, are formed alongside well-defined rectangular pits of monoatomic depth.…”
Section: (B) Surface Structuresmentioning
confidence: 99%
“…For example, AFM images shown in fig. 1 in Barth & Henry (2003) demonstrate that irregular adstructures, reminiscent of debris on the rough surface shown in figure 6, are formed alongside well-defined rectangular pits of monoatomic depth.…”
Section: (B) Surface Structuresmentioning
confidence: 99%
“…Atomic force microscopy (AFM) studies operated in the so-called noncontact mode (NC-AFM) have recently been successfully employed for atomic-scale studies of a range of clean metal oxide insulating surfaces, [17][18][19] such as α-Al 2 O 3 (0001) [20][21][22] or MgO. 23,24 Very recently, we used NC-AFM to resolve the atomic-scale surface structure of the MgAl 2 O 4 (100) surface. 7 The studies in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…This is a clear indication that defects play an important role in the growth process. It is well known that oxide surfaces tend to have a high density of point defects (typical estimates being 10 12 -10 13 cm À2 [31]) in addition to steps and grain boundaries. HREELS spectra have been assigned and interpreted in terms of neutral oxygen vacancies, so called F-centers, where an oxygen atom has been removed from the surface [32].…”
Section: Introductionmentioning
confidence: 99%
“…HREELS spectra have been assigned and interpreted in terms of neutral oxygen vacancies, so called F-centers, where an oxygen atom has been removed from the surface [32]. It has also been suggested that di-vacancies are present where both a Mg-and O-atom are missing [31] and, in some cases, charged oxygen vacancies [32,33]. We have assumed that the defects nucleating Pd clusters are neutral oxygen vacancies.…”
Section: Introductionmentioning
confidence: 99%